Functional Health Status in Oropharyngeal Dysphagia - Speyer, R.; Kertscher, B.; Cordier, Reinie (A C T Publishing Group Limited, 2014)
Patient self-evaluations on Functional Health Status (FHS) questionnaires are considered to be part of the assessment of oropharyngeal dysphagia. FHS questionnaires capture the unique personal perception of someone’s health, taking into account social, functional and psychological factors. Many FHS questionnaires have been reported on in literature. This paper describes a selection of FHS questionnaires in more detail; issues concerning the inclusion of Health Related Quality of Life (HRQOL) items, choices in target populations and the distinction between oropharyngeal versus esophageal dysphagia will be discussed. Recommendations are made about the evaluation and use of FHS questionnaires in daily clinical practice. In particular the psychometric properties of FHS questionnaires should be evaluated to determine if they meet quality criteria for measurement properties of health status questionnaires in order to guarantee valid and reliable outcome measurements.